Analysis of Accounting Information System of Raw Material Inventories Perumda Tirta Hidayah Bengkulu City - Fenita Depriyanda Putri; Ida Anggriani; Rinto Noviantoro (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
Method of analysis used in this study is a comparative method. Comparative Research is a study that compares the existence of one or more variables in two different samples. Where in this study the researchers compared one variable with two different objects. The results showed that the accounting information system for the inventory of raw materials at Perumda Tirta Hidayah, Bengkulu City, includes transactions for business use, system classification, production cycles. For transaction processes in Perumda Tirta Hidavah, Bengkulu City, such as the purchase process. the process of changing, the process of providing goods. For the use of SIA for businesses related to Perumda Tirta Hidayah are able to improve products or services, can cope with running out of raw materials, can provide the right information While the classification of related systems at Perumda Tirta Hidayah is about open and closed systems, man-made or artificial systems God, and a system whose performance can be ensured, And there is also a production cycle involved in Perumda Tirta Hidayah Bengkulu City in the production orders for the raw materials needed, payment of salaries, the product process is complete. This production cycle has a match and a discrepancy as the salaries of permanent employees are not paid based on the same absences that exist in the production cycle in the TMBooks book.